Child and Maternal Factors Related to Under-5 Mortality in the Philippines (Journal of Namibian Studies : History Politics Culture, 2023)
Child health is a crucial proxy and indicator of human development in a country. That is why reducing child deaths, specifically under-5 (U5) mortality, is the goal of all the member-states of the United Nations in the 2030 Agenda for Sustainable Development. Despite the gradual decrease of under-5 deaths, the Philippines lacks empirical evidence on the factors related to under-5 mortality. A descriptive analysis of the Kids Recode (KR) file contained in the 2017 Philippine Demographic and Health Survey (NDHS) was conducted using Stata version 14. From 9,908 women (weighted) of reproductive age 15-49 with at least one child younger than five years old, the study found that child deaths were higher among males and children who were born later in birth order. In terms of maternal factors, the U-5 mortality was prevalent among children whose mothers were in their 40s, had little/no education, lived in rural areas, and came from poor households. Similarly, child survival was lower among mothers who had high parity (more than 3 children), were employed, had short birth spacing (